Travessias do fantástico e transformações no Brasil: o caso Machado de Assis - Fernandes, Marcos Túlio (2019)
The present thesis has researched the crossings of the French translations of the narratives of E. T. A. Hoffmann and the resignifications of his leitmotiv in the production of Machado de Assis’s tales of the fantastic. The editorial success of the German Romantic author in Paris has spurred the fashion of the fantastic tale in France and promoted the import of his fantastic literature into the Brazilian cultural space, stimulating the emergence of national translations and the production of the genre by our writers until the fantastic tale became fashionable in the pages of our periodical press from the 1860s, at which time the Brazilian writer began writing strange fantasies destined, for the most part, to the periodicals of female profiles. Object of discussion among scholars of the genre, the fantastic of Machado de Assis has often been seen as a labile genre that does not reach the effect of European writers. This conception based only on immanent criteria instigated us to go in another direction and to support our research in the methodological concepts of Cultural Transfers (ESPAGNE, 2012) that allow us to understand Machado's fantastic as a genre of its own, original and not to be overlooked, as seen as a copy or imitation, because the Brazilian author, inspired by the translations of Hoffmann, renamed themes and concepts as a strategy to meet the expectations of his readers, since the translations are no less legitimate than their originals and the concepts inherent in cultural objects do not suffer losses when they cross borders. The research aimed to observe the presence of the fantastic of Hoffmann in the cultural scene of the country and to understand the fantastic tale of the Brazilian writer as aesthetic tessitura without, however, to detach it from its condition of merchandise. The corpus was composed of unusual narratives published between 1862 and 1892 in the periodicals - Jornal das Famílias, O Futuro, A Época, A Estação, O Cruzeiro - that implied in the production of different concepts of fantastic that cannot be observed only by categories immanent to the textual fabric, proper to the structuralist conceptions of fantastic theorists, among whom Todorov (1970) has been a reference. We have analyzed the transformations of literary borrowings in order to fill in cracks and to trim critical-academic edges around the fantastic of Machado, whose meaning, like any other genre of the 19th century, does not dissociate itself from the materiality of its supports. Our results have demonstrated the insufficiency of the intratextual criteria to define a type of fantasy, created according to editorial guidelines and in accordance with current cultural poetics, since even when it was a publication of a single story published by different periodicals, both of female profiles, the author needed to adapt it to the editorial guidelines of each support. In this sense, our contribution to the area of Translation and Cultural Studies of Literature is to demonstrate that the machadian fantastic was always adjusted to editorial and cultural conditions that required the Wizard of Cosme Velho to manipulate fantastic formulas according to the profile of each support by which his tales were told.